Prostate Cancer: genetics in practice now and in the future - Jana McHugh; Elizabeth Bancroft; Zsofia Kote-Jarai; Rosalind Eeles (Hereditary Cancer in Clinical Practice)
Abstract Prostate Cancer (PrCa) is one of the most common cancers worldwide and causes a significant healthcare burden. Recent predictions estimate the incidence of new cases of PrCa will double from 1.4 million in 2020 to 2.9 million by 2040. The known risk factors for PrCa are increasing age, family history, ancestry and genetics. PrCa is one of the most heritable of the more common cancers. The heritability of PrCa is due to both rare moderate to high-risk monogenic variants and more common variants known as single nucleotide polymorphisms (SNPs) which can be used to calculate a polygenic risk score (PRS) for PrCa, while there is some of the genetic risk as yet unexplained. In recent years more PrCa risk-associated SNPs have been identified, increasing over time with the inclusion of more persons of diverse ancestry in studies. The identification of germline variants known to be associated with increased PrCa risk and disease aggressiveness has led to targeted treatments for certain pathogenic variant carriers. This is a mini review of how the genetics of PrCa can impact on screening and early detection of the disease and the treatment and management of the disease when diagnosed.